THYROID GLAND STRUCTURE, FUNCTION AND DEFICIENCY - Rashidov Shamsiddin Sharofovich; Yusupov Azizbek Mirsharof o‘g‘li; Yo‘ldoshev Shohjahon Jumanazar o‘g‘li; Zafarova Vazira Alisher qizi; Pardayeva Dilnavo Abduxoliq qizi (Web of Journals Publishing, 2023)
The thyroid gland is a butterfly-shaped organ located at the base of the neck. It releases hormones that control metabolism—the way your body uses energy. Thyroid hormones regulate the vital functions of the body. The thyroid gland is about 2 inches long and is located in the front of your throat, below the thyroid cartilage, sometimes called the Adam's apple. The thyroid gland has two sides that lie on either side of your airway and are usually connected by a band of thyroid tissue known as the isthmus. Some people have no isthmus and instead have two separate thyroid lobes. This gland is responsible for the secretion of thyroid hormone (thyroxine). If there is a problem with the thyroid gland, it should be treated in time and should not be ignored. Thyroid hormone is an important hormone for fetal or growth development and also plays an important role in the control of body temperature, muscle tone and strength, growth hormone secretion, and emotional state in adults. Therefore, our body regulates the amount of thyroid hormone to maintain a normal amount at all times, so that there is no excess or deficiency. Insufficiency of the function of the thyroid gland, as we mentioned above, leads to various negative consequences. In order to prevent such problems, it is very important for everyone to have information about the thyroid gland, how its initial symptoms are, and to consult a doctor in time to prevent such negative consequences. Do not be indifferent to your health.
Keywords: Thyroid gland, thyroxine, isthmus, metamorphosis, metabolism, pituitary gland, T3, T4, hypothyroidism, hyperthyroidism, thyroiditis.Usually, hereditary and acquired forms of hemolytic anemia are distinguished. Under physiological conditions, erythrocytes live 100-120 days. Then, the pigment free bilirubin formed as a result of the breakdown of erythrocytes by macrophages in the spleen, which loses its deformability, circulates in the blood and goes to the liver, where it binds with glucuronic acid with the help of enzymes. Bilirubin glucuronide enters the intestine as part of bile.